The relationship between functional status and mental–emotional health among adults aged 40 years and older - Muh. Amri Arfandi; Muhamad Zakki Saefurrohim; Irfansyah Baharuddin Pakki; Siswanto Siswanto; Risva Risva (JOURNAL OF Mental Health Concerns, 2026)
Background: Mental–emotional problems frequently remain undetected among middle-aged and older adults. Declining functional status associated with aging contributes to increased mental-emotional symptoms. Purpose: To examine the relationship between functional status and mental–emotional symptoms among adults aged 40 years and older. Method: This cross-sectional study involved 128 adults aged 40 years and older in Samarinda, Indonesia. Functional status was assessed using the Barthel Index (BI) and mental-emotional health using the Self-Reporting Questionnaire-20 (SRQ-20). Analyses included Fisher Exact test, Mann-Whitney U test, and Spearman correlation. Results: Participants, 19.5% had functional dependency and 22.7% screened positive for MED. The median SRQ score in the dependent group (5.0) was significantly higher than the independent group (2.0; p=0.001). A significant negative correlation was found between BI and SRQ scores (r=-0.322; p=0.0002). OR for MED in the dependent group was 2.334 (95% CI: 0.901–6.045). Conclusion: Poorer functional status was associated with a greater burden of mental–emotional symptoms. However, the categorical association between dependency and positive screening was not statistically significant. Integrated functional and mental-health screening may be useful in primary care for middle-aged and older adults. Keywords: Barthel Index; Functional Status; Mental–Emotional Symptoms; Older Adults; SRQ-20.